2018
DOI: 10.1093/tbm/ibx056
|View full text |Cite
|
Sign up to set email alerts
|

The research participant perspective related to the conduct of genomic cohort studies: A systematic review of the quantitative literature

Abstract: Observational genome-wide association studies require large sample sizes. Evaluating the interplay between genomic, environmental, and lifestyle factors can require even larger sample sizes. The All of Us Research Program will recruit 1 million participants to facilitate research on genomic, environmental, and lifestyle factors. Integrating participant preferences into the research process is a new paradigm and a necessary component of the All of Us Research Program. The purpose of the study is to summarize qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Public, patient, and participant perspectives on biobank and genomic cohort research have been the frequent subject of previous research [22][23][24][25]. These studies have oftentimes been conducted using a narrative description of the research endeavor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Public, patient, and participant perspectives on biobank and genomic cohort research have been the frequent subject of previous research [22][23][24][25]. These studies have oftentimes been conducted using a narrative description of the research endeavor.…”
Section: Discussionmentioning
confidence: 99%
“…I think this is one of my favorite ones out of all of them because it's showing … the breakdown of it … It's really interesting to see-this shows me what they're looking for. (24) This included the possibility that new products might be developed:…”
Section: Sentences Highlighted As Reassuringmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, some studies enroll patients who are from the general population of patients in both hospital and nonhospital setting (Sanderson et al, 2013;Walker et al, 2014;Jones et al, 2017), while others assess factors associated with participation among patients with specific diseases (Parikh et al, 2017). This is an important distinction as motivational factors vary considerably depending on the type of study and population (e.g., clinical trial vs. observational study, disease group vs. healthy population) (Goodman et al, 2018;Goodman et al, 2019). Further, the set of reasons that motivate healthy individuals to participate is likely very different from reasons that motivate individuals with specific diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Research participants, genomic researchers, and Institutional Review Board (IRB) professionals held differing perspectives, with researchers reporting less concern than participants or IRB professionals about the possibility that participants could be personally identified or harmed from a study involving de-identified data. Expanding on participant perspectives, a second work by Goodman et al [18] conducted a systematic review to identify participant views related to consent, use of de-identified genomic data, and return of individual genomic results. While most participants supported the return of individual genomic results and broad informed consent, differences in views about consent were evident across participant age and gender.…”
mentioning
confidence: 99%